Farm Laws in India: Reasoning, Consequences, and Way Ahead for Agricultural Reforms - Raste, Arun (Digital Repository of Theses - SSBM Geneva, 2025)
This study examines India’s 2020–21 farm laws, analyzing their objectives, socio-economic impact, and implications for agricultural reform in one of the world’s most agrarian economies. Employing a mixed-methods approach, the research integrates structured surveys of 347 farmers with in-depth interviews of policymakers, economists, and agricultural experts. It also draws on policy documents, market reports, and case studies to assess the laws' effects on farmer incomes, market efficiency, rural livelihoods, and alignment with global sustainability goals. Findings reveal that while the reforms aimed to modernize agriculture, enhance investment, and streamline markets, they generated widespread concern among small and marginal farmers. Key issues include the potential erosion of the Minimum Support Price (MSP) system, risks in contract farming, and fears of corporate dominance. Resistance was strongest in states dependent on Agricultural Produce Market Committees (APMCs). The research identifies both opportunities and risks: improved market access and reduced intermediaries on one hand, and increased vulnerability for disadvantaged farmers on the other. It calls for policy revisions to ensure equity and protection, including strengthening APMCs, securing contract farming agreements, and leveraging digital tools to enhance market integration. The study aims to emphasizes inclusive, participatory reforms that prioritize social justice and resilience. It offers strategic recommendations to balance modernization goals with rural socio-economic realities and ensure that agricultural reforms contribute to a sustainable and equitable future.